HUBUNGAN PENGGUNAAN AIR BERSIH DAN JAMBAN KELUARGA DENGAN KEJADIAN DIARE PADA BALITA - Hamzah B; Strahmawati Hamzah (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
ABSTRACT Diarrhea is still a health problem in the world, there are about 2 million cases of diarrhea worldwide every year, and 1,9 million children under five years die from diarrhea every year. Diarrhea in Indonesia is an endemic disease and it is very potential for Extraordinary Events to occur. Diarrhea was the 3rd highest infectious disease in North Sulawesi in 2016 with a total of 23,881 cases. This study aims to analyze the relationship between the use of clean water and the use of latrines with the incidence of diarrhea in children under five in Gogagoman Village, Kotamobagu City. This study used a cross sectional study design with a total sample of 130 children under five. The subject of this research is the mother/the closest person to the toddler. The sampling technique used is simple random sampling. The data collection instrument used a questionnaire and an observation sheet. The data were then analyzed by univariate and bivariate using chi square test. The results showed that there was a relationship between the use of clean water and the incidence of diarrhea in children under five (p = 0,036